2014
DOI: 10.1002/acp.3042
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Conspiracy Theories, Paranormal Beliefs, and Pseudoscience Acceptance Among a University Population

Abstract: SummaryVery little research has investigated whether believing in paranormal, conspiracy, and pseudoscientific claims are related, even though they share the property of having no epistemic warrant. The present study investigated the association between these categories of epistemically unwarranted beliefs. Results revealed moderate to strong positive correlations between the three categories of epistemically unwarranted beliefs, suggesting that believers in one type tended to also endorse other types. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
296
1
15

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(345 citation statements)
references
References 48 publications
33
296
1
15
Order By: Relevance
“…Psychology tests (locus of control, magical ideation, referential thinking, Tellegen absorption scale) and the Tobacyk paranormal belief scale have all been validated; however, because a new section of questions concerning detoxification was added to the paranormal belief scale, the belief scale had to be measured for reliability using Cronbach's alpha (Lobato et al 2014). The overall reliability of the entire paranormal belief test as well as the reliability of each subcategory of questions was tested.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychology tests (locus of control, magical ideation, referential thinking, Tellegen absorption scale) and the Tobacyk paranormal belief scale have all been validated; however, because a new section of questions concerning detoxification was added to the paranormal belief scale, the belief scale had to be measured for reliability using Cronbach's alpha (Lobato et al 2014). The overall reliability of the entire paranormal belief test as well as the reliability of each subcategory of questions was tested.…”
Section: Discussionmentioning
confidence: 99%
“…These psychological tests included the Locus of Control (Rotter 1966), a measure of the relative internal vs. external control a person imparts to their life; Magical Ideation (Eckblad and Chapman 1983), a measurement of belief in magically controlled causation; Referential Thinking (Lenzenweger et al 1997), an index of how likely an individual is to perceive unrelated events as pertaining directly to themselves; and a Tellegen Absorption Scale (Tellegen and Atkinson 1974) which includes three submeasures: absorption (complete attention to a subject/object, either real or fantasy), stability (ability to alter impulses based on the situation), and introversion (impulse resistance/expression). Each of these tests has been linked to beliefs in paranormal and/or pseudoscientific beliefs (Peltzer 2003;Swami et al 2011;Lobato et al 2014).…”
Section: Measurement Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this perspective, studies have reported positive associations between belief in conspiracy theories and traits including paranoia, magical ideation, and belief in the paranormal (e.g., Brotherton & Eser, 2014;Lobato, Mendoza, Sims, & Chin, 2014;Stieger, Gumhalter, Tran, Voracek, & Swami, 2013;Swami et al, 2011). In explanation, it has been suggested that conspiracy theories and anomalous beliefs share features in common (e.g., both overly rely on intuitive-experiential processing of information and lack rigorous, selfgenerated testing; Swami, Voracek, Stieger, Tran & Furnham, 2014) and that endorsement of one set of anomalous beliefs (e.g., belief in the paranormal) makes acceptance of other anomalous beliefs (e.g., conspiracy theories) more likely (Ramsay, 2006).…”
Section: Conspiracy Theoriesmentioning
confidence: 97%
“…Numerous personality factors, emotional states and social political attitudes have been found to correlate with support for CTs, including anomia (broadly: distrust towards authorities, feelings of powerlessness, and feelings of dissatisfaction about one's life; [19][20][21][22][23][24][25][26][27][28], personal and social (i.e., feeling of insecurity) anxiety [29][30][31], negative self-esteem [19,22,26,32], paranoia and schizotypy [16,21,26,28,[33][34][35][36][37], Right-Wing Authoritarianism [19,28,32,38]; but only marginally in [39], and irrationality or paranormal beliefs [16,21,24,26,28,30,35,[40][41][42][43][44]. Motivational processes have also been underlined.…”
Section: Conspiracy Theories (Cts) In Psychologymentioning
confidence: 99%